Report of the Working Group on Handicrafts Seventh Five Year Plan (1985-90) - Planning Commission (Planning Commission, 1984)
The Government of India (Planning Commission) vide their Office Memorandum No. VSI/34(10)/83 dated the 10th August, 1983 and letter of even number dated the 18th November, 1983 constituted a Working Group on Handicrafts under the Chairmanship of Shri Mani Narayanaswami, Secretary(Textiles), Ministry of Commerce and Vice-Chairmanship of Shri Shiromani Sharma, Development Commissioner(Handicrafts) in order to facilitate formulation of policies and programmes for the development of handicrafts sector for the Seventh Five Year Plan (1985-90) and to make a critical review of the programmes carried out during the Sixth Plan (1980-85).
Government of India, Ministry of Commerce